Exploring the role of gaze behaviour in socially shared regulation of collaborative learning in a group task - Whitehead, Ridwan; Nguyen, Andy; Järvelä, Sanna (Journal of computer assisted learning, 2024)
Background The necessity of supporting socially shared regulation of learning (SSRL) for learners is widely acknowledged as a crucial element for successful collaborative learning (CL). However, inherent challenges are presented for the observation, study, and support of SSRL. Non‐verbal behaviours have been identified as a potentially rich resource for understanding learner interactions within CL. Yet, the exploration of its impact on SSRL remains largely unexplored. Objective The present study aims to explore how gaze behaviour, as a non‐verbal behaviour, relates to verbal interactions that characterise SSRL in CL. Methods Twenty‐seven Finnish secondary school students were given a 30‐min group task of creating a breakfast smoothie, in which trigger events were integrated to examine possible interactions that characterise SSRL. In this experimental setting, data from multiple modalities were collected. For analysis, process mining was used to explore patterns of interaction, and multidimensional recurrence quantification analysis (MdRQA) was used, alongside with statistical analysis. Results and Conclusions Our study revealed that gaze behaviour is intricately linked with SSRL interactions, suggesting a complex interplay in collaborative learning contexts. When temporally investigated, SSRL interactions varied in frequency while gaze behaviour remained constant. Moreover, the recurrence of gaze and SSRL interactions did not vary due to trigger events, confirming an established collaborative pattern. Implications This study advances the field by extending research on SSRL by introducing a ‘non‐verbal perspective’. This perspective enriches our understanding of collaborative learning environments by revealing hidden interaction patterns and guiding the development of more responsive and adaptive digital learning tools. Lay Description What is currently known? Socially shared regulation of learning (SSRL) is crucial for successful learning to occur in collaborative learning (CL). SSRL is inherently difficult to observe, study, and support. Non‐verbal behaviours have been found to tell a lot about how learners interact in CL context. SSRL related interactions have not been examined in relation to non‐verbal behaviours, which might tell more about learners in CL. What does this paper add? Using process mining, our study explored how gaze behaviour (i.e., looking at each other, laptop, or other) can signal certain interactions that characterise SSRL. The frequency of gaze behaviour remains consistent throughout trigger events, moments that require learners to adapt to challenges, while verbal interactions varied. Recurrence patterns of learners remains consistent throughout trigger events, indicating established patterns throughout CL. Implications for practice? CL is a complex process which involves several intersections of verbal and nonverbal channels as learners interact with one another. By considering gaze behaviour, stakeholders in education can understand better where support is needed. Using multimodal and multichannel approaches can provide more detail into the interactions between learners in CL.